1996
DOI: 10.1111/j.1745-9125.1996.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Strain: An Examination of Delinquent Coping Responses*

Abstract: Strain theories have conceptualized delinquency as a form of adaptive, problem-solving behavior, usually committed in response to problems involving frustrating and undesirable social environments. The most recent version of strain theory, Agnew's general strain theory, provides the most complete formulation of this argument by suggesting that delinquent behavior enables adolescents to cope with the socioemotional problems generated by negative social relations. To date, however, the actual coping effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
169
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(186 citation statements)
references
References 21 publications
14
169
1
2
Order By: Relevance
“…Other tests of general strain theory have found support for specific components of general strain (see Brezina, 1996;Mazerolle & Piquero, 1997, 1998 and support among different populations of offenders (see Broidy, 2001;Piquero & Sealock, 2000;Broidy & Agnew, 1997). The diversity of these tests provides confirmation that the theory should be tested more explicitly and completely with appropriate data drawn from an appropriate sample within an appropriate context.…”
Section: Figurementioning
confidence: 97%
“…Other tests of general strain theory have found support for specific components of general strain (see Brezina, 1996;Mazerolle & Piquero, 1997, 1998 and support among different populations of offenders (see Broidy, 2001;Piquero & Sealock, 2000;Broidy & Agnew, 1997). The diversity of these tests provides confirmation that the theory should be tested more explicitly and completely with appropriate data drawn from an appropriate sample within an appropriate context.…”
Section: Figurementioning
confidence: 97%
“…Research has failed to find consistent support for the conditioning hypothesis of GST in explaining delinquency (e.g., Agnew & White, 1992;Aseltine et al, 2000;Brezina, 1996;Hay, 2003;Hoffmann & Miller, 1998;Mazerolle & Maahs, 2000;Paternoster & Mazerolle, 1994;Piquero & Sealock, 2000;Robbers, 2004). A number of possible conditioning factors have been examined including social support (e.g., Robbers, 2004), self-esteem (e.g., Hoffmann & Miller, 1998), depression (e.g., Piquero & Sealock, 2000), anger (e.g., Hay, 2003), delinquent peer exposure (e.g., Piquero & Sealock, 2004), religiosity (e.g., Jang & Johnson, 2005), and others.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
“…Several tests of GST relating to delinquency have included self-esteem as a conditioning variable (Aseltine et al, 2000;Brezina, 1996;Hoffmann & Cerbone, 1999;Hoffmann & Miller, 1998). Using data from a study conducted in a large midwestern city in the United States, Hoffmann and Miller (1998) performed a longitudinal test of GST that examined, among other things, the impact of self-esteem on the relationship between negative life events and delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
“…Although past studies have found that major depression is highly associated with violent behavior and crime (Hodgins, 1993;Robins, 1993;Steadman et al, 1998;Stueve & Link, 1997), the precise nature of this relationship has not been explored. Individuals may try to alleviate depression by engaging in illegal acts (Agnew, 1992;Brezina, 1996Brezina, , 2000, or the association could be spurious since depression and law violation may have a common antecedent and result from a similar process (Coster & Heimer, 2001). In contrast, studies have indicated that other internalizing disorders, such as PTSD, are not associated with criminality.…”
Section: Mental Disorder Comorbidity and Criminalitymentioning
confidence: 99%